Study of aramid and carbon fibers on the tensile properties of early strength cement mortar. Issue 3 (May 2019) - Nie, Liangxue; Xu, Jinyu; Luo, Xin; Chen, Haowen; Chang, Sen; Wang, Tengjiao; Liu, Gaojie
Abstract: The sulfoaluminate cement was used to prepare the high early strength cement mortar specimens (HESCM) with 0.1%, 0.2% and 0.3% volume content of aramid and carbon fibers, and the contrastive studies of the specimens on compressive and tensile properties were presented in this paper by using of universal testing machine and electronic precision servo tensile test machine. The tests reveal that the addition of aramid and carbon fibers has a positive effect on compressive strength, tensile strength, tensile strain and tensile toughness of specimen, and the bigger the volume content of fiber, the more significant on improvement. What's further, the tensile toughness has the maximum improvement, while the compressive strength increases minimum, and aramid fiber produces a better improving effect on these properties than that of carbon fiber.